Changes in cognitive function and cerebral oxygenation patterns in rugby and non-contact sportspersons over a 15-week season - Clark, A. (Stellenbosch University, 2018)
Rugby is a contact team sport and is one of the most popular sports in South Africa and internationally. Recently, a growing body of research has highlighted that repeated concussive and subconcussive head contacts suffered during contact sport participation may have implications on athletes` health later in life. Of particular concern is the notion that the accumulation of these blows to the head may spark progressive neurodegeneration in the form of diseases such as chronic traumatic encephalopathy (CTE). Despite these concerns, the focus of research in rugby appears to be on the diagnosis and acute treatment of concussive injury, with little thought given to the long-term consequences. The purpose of this study was to broaden our understanding of the effect of short-term exposure to physical contact on the brains of rugby players who participate in high-level contact sport competition. The primary aim of the study was to determine whether a fifteen-week season elicit a change in the cognitive function and cerebral oxygenation of rugby players when compared with age and sex matched non-contact athletes. The secondary aim was to determine whether changes in sleep quantity and quality, as well as mood states, took place that have the potential to impact the cognitive function and cerebral oxygenation of the participants. Twenty-nine university athletes (16 rugby players (21,3 ± 1,35 yrs) and 13 non-contact sport athletes (20,8 ± 1,97 yrs)) were assessed before and after the 2017 Varsity Cup rugby competition (± 15 weeks). Each participant completed the CNS Vital Signs® Core testing battery, with measurements of cerebral oxyhaemoglobin (?[O2Hb]), deoxyhaemoglobin (?[HHb]), tissue oxygenation index (TOI) and normalised total haemoglobin index (nTHI) conducted simultaneously throughout testing. The cognitive testing battery consisted of seven tests that assessed eleven cognitive domains, giving an overall estimate of cognitive function. Additionally, participants` mood states and sleep status (quality and quantity) were measured prior to cognitive and cerebral oxygenation analysis each session. Overall, cognitive function did not change for either group over the 15-week season (ES = 0,11 and 0,06 for Rugby and Control, respectively). Cerebral oxygenation measurements did not reflect any unexpected changes within the Control group, however, relative ?[HHb] (ES = 0,57) and nTHI (P = 0,01; ES = 1,29) were significantly increased at post-testing in the rugby players. These variables are considered indirect indicators of oxygen consumption and cerebral blood flow rate, respectively. Thus, while the rugby players` cognitive performance was maintained, alterations to cerebral oxygenation data took place that may be the result of participation in their sport. These findings may suggest that subtle impairments are beginning to take place within the brains of the players. Therefore, although a 15-week season may not have been enough to induce obvious negative changes in rugby players` cognitive function, exposure to contact over the course of multiple seasons may cause neural impairments to the extent that cognitive function, and health, are affected later in life. Despite these notions, it is recognised that changes in mood state and sleep pattern of the players may have confounded the results. Thus, additional research is required to further build on the sentiments proposed in this study.